The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ophtha.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Reliability of Standard Automated Perimetry in Regions of Glaucomatous Damage

Abstract: Purpose Visual field testing uses high contrast stimuli in areas of severe visual field loss. However, retinal ganglion cells saturate with high contrast stimuli, suggesting that the probability of detecting perimetric stimuli may not increase indefinitely as contrast increases. Driven by this concept, this study examines the lower limit of perimetric sensitivity for reliable testing by standard automated perimetry. Design Evaluation of diagnostic test. Participants 34 participants with moderate to severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
200
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(216 citation statements)
references
References 41 publications
9
200
3
1
Order By: Relevance
“…12 Participants with moderate to severe primary open-angle glaucoma were recruited from a tertiary glaucoma clinic at Devers Eye Institute (Portland, OR). Inclusion criteria were a diagnosis of primary open-angle glaucoma as determined by each participant's clinician, and at least two nonadjacent visual field locations with sensitivities between 6 and 18 dB on both of their two most recent clinic visits (24-2 test pattern, size III stimulus, SITA Standard algorithm; Humphrey Field Analyzer [HFA]; Carl-Zeiss Meditec, Dublin, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Participants with moderate to severe primary open-angle glaucoma were recruited from a tertiary glaucoma clinic at Devers Eye Institute (Portland, OR). Inclusion criteria were a diagnosis of primary open-angle glaucoma as determined by each participant's clinician, and at least two nonadjacent visual field locations with sensitivities between 6 and 18 dB on both of their two most recent clinic visits (24-2 test pattern, size III stimulus, SITA Standard algorithm; Humphrey Field Analyzer [HFA]; Carl-Zeiss Meditec, Dublin, CA).…”
Section: Methodsmentioning
confidence: 99%
“…12 For example, the probability that participants responded to a 20,000% (2 dB) contrast in a deep visual field defect was typically only slightly higher than the probability that they would respond to a 2000% (12 dB) contrast at the same location (this small increase may reflect effects of light from the stimulus being scattered toward remaining areas of higher sensitivity). For locations with sensitivity worse than 15 to 19 dB (equivalent to contrasts of 1000%-400%), we found that the relation between sensitivity measures from FOS curves and those obtained from clinical perimetry had R 2 less than 0.1, indicating that the true sensitivity explained less than 10% of the observed variance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Many papers have described the large variability in VF measurements and the increasing variability as sensitivity declines. [7][8][9] Gardiner et al 73 found that sensitivity values below a cut-off value of between 15 and 19 dB are particularly unreliable and that values at these levels of sensitivity agree poorly with estimates obtained from 'frequency of seeing' curves. Gardiner et al 73 also discussed the concept that sensitivity values may not be truly defined at such low levels, as the retinal ganglion cells remaining cannot be stimulated sufficiently to produce a 50% response rate to stimuli, regardless of the intensity of the presentation.…”
Section: Review Of Models To Identify Visual Field Deterioration Andmentioning
confidence: 99%
“…[7][8][9] Gardiner et al 73 found that sensitivity values below a cut-off value of between 15 and 19 dB are particularly unreliable and that values at these levels of sensitivity agree poorly with estimates obtained from 'frequency of seeing' curves. Gardiner et al 73 also discussed the concept that sensitivity values may not be truly defined at such low levels, as the retinal ganglion cells remaining cannot be stimulated sufficiently to produce a 50% response rate to stimuli, regardless of the intensity of the presentation. Gardiner et al 74 found that the proportion of eyes identified as deteriorating was not decreased by truncating sensitivities at 10 dB (i.e.…”
Section: Review Of Models To Identify Visual Field Deterioration Andmentioning
confidence: 99%